Comparison of the RIPASA and Labeda Scoring Systems to Assess the Morphological Severity of Acute Appendicitis - Pattiiha, Abdul Muthalib; Selomo, Prita Aulia M.; Faruk, Muhammad (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Acute appendicitis is the most common emergency surgical case, leading to further complications if not treated immediately. Limited diagnostics infrastructure is an obstacle in developing countries, especially in the regions. Therefore, alternatives such as clinical scoring systems are required to assist in diagnosis. AIM: This study aimed to compare the use of the RIPASA and Labeda scores to assess the severity of acute appendicitis morphology by determining the accuracy, sensitivity, specificity, positive predictive value, negative predictive value, and negative appendectomy rate. METHODS: This was a cross-sectional study designed to assess the severity of morphology of intra-operative acute appendicitis in Dr. Chasan Boesoirie Hospital and network hospitals in Ternate, North Maluku, Indonesia. Data regarding patient characteristics, leukocytes, and acute appendicitis severity were collected and analyzed alongside RIPASA and Labeda scores using the Chi-square test. p < 0.05 were considered statistically significant. RESULTS: Of 59 cases, 39 (66.1%) were complicated acute appendicitis and 20 (33.9%) were noncomplicated acute appendicitis. Chi-square test results showed that there was a significant relationship (p ≤ 0.001) between RIPASA/Labeda scores and the severity of acute appendicitis morphology. CONCLUSION: RIPASA and Labeda scores had the same accuracy, sensitivity, specificity, positive predictive value, and negative predictive value for acute appendicitis severity. Thus, RIPASA and Labeda scores can be used by physicians to help establish a diagnosis of acute appendicitis and determine the need for emergency surgery, as well as predict the possibility of morbidity/complications in patients.